2022
DOI: 10.1186/s12872-022-02833-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course, viral etiology, and the diagnostic workup for patients with suspected myocarditis: a single-center prospective study

Abstract: Background Myocarditis is a highly heterogeneous disorder with a challenging diagnostic work-up. We aimed to focus on the possible diagnostic workup for this condition in settings where endomyocardial biopsy as a gold standard is not always feasible, detect the etiologic cardiotropic viruses in our locality, and follow the clinical course in patients admitted with clinically suspected myocarditis. Methods This is a prospective observational study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Although viral myocarditis is thought to be the most common infectious aetiology of acute myocarditis 26 , 29 , the pathophysiologic mechanisms responsible for myocardial injury & necrosis are not yet fully understood. Some studies have also reported ischemia without significant coronary artery disease as a possible cause which is indicative of coagulopathies 30 , 31 . Endomyocardial biopsy, the gold standard modality for the diagnosis of acute myocarditis, is an invasive technique due to which limited data is available on biopsy findings.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Although viral myocarditis is thought to be the most common infectious aetiology of acute myocarditis 26 , 29 , the pathophysiologic mechanisms responsible for myocardial injury & necrosis are not yet fully understood. Some studies have also reported ischemia without significant coronary artery disease as a possible cause which is indicative of coagulopathies 30 , 31 . Endomyocardial biopsy, the gold standard modality for the diagnosis of acute myocarditis, is an invasive technique due to which limited data is available on biopsy findings.…”
Section: Pathophysiologymentioning
confidence: 99%